2020
DOI: 10.32861/jssr.62.133.139
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Food Security Status amongst Smallholder Farmers Utilizing Different Maize Varieties in OR Tambo District, South Africa

Abstract: Maize is an important staple crop for poverty reduction and global food security in Sub Saharan Africa. Food insecurity can be combated through adoption of productivity improving technologies, which include improved maize varieties. In that endeavour, South Africa has promoted various improved maize varieties which include open pollinated varieties (OPVs), hybrids, and genetically modified (GM) varieties. Despite this, the traditional landrace varieties have also been dominating in the country. However, the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Maize yields were below the national average, which often fluctuates between 4000 kg/ha and 7000 kg/ha [61][62][63]. Low yields in ORTDM, and other smallholder farming areas in South Africa, are also reported by Chimonyo et al [64] and by Kambanje et al [65].…”
Section: Relationship Of Yield With Rainfall and Ndvimentioning
confidence: 82%
“…Maize yields were below the national average, which often fluctuates between 4000 kg/ha and 7000 kg/ha [61][62][63]. Low yields in ORTDM, and other smallholder farming areas in South Africa, are also reported by Chimonyo et al [64] and by Kambanje et al [65].…”
Section: Relationship Of Yield With Rainfall and Ndvimentioning
confidence: 82%
“…Over the 3-year period between 2018 and 2020, maize yields ranged between 367.10 and 7449.13 kg/ha with an average of 3259.16 kg/ha (Table 2), which reveals that most farmers produced below the national average, which often ranges from 4700 to more than 7000 kg/ha [49][50][51]. Other studies also reported that maize yields in ORTDM and the Eastern Cape province at large are low and less than potential [52][53][54]. The most important input influencing yield was seed variety.…”
Section: Discussionmentioning
confidence: 99%
“…40 Although their yields are claimed to be low, Landrace maize cultivars are widely produced in rural South Africa for a variety of reasons to include low seed cost and tolerance to harsh agro-ecology. 4 …”
Section: Improved Open Pollinated Varietiesmentioning
confidence: 99%
“…Previous studies also noted high usage of Landrace maize cultivars in rural areas because of their adaptability to local conditions and yield stability. 4 , 31 , 32
Figure 2. Production status of maize cultivars from the study area.
…”
Section: Maize Cultivars Grown From the Study Areamentioning
confidence: 99%
See 1 more Smart Citation